CONTRIBUTION TO DEFINING INTEGRITY TESTING IN POLICE – NORMATIVE ASPECTS - Marinković, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
CONTRIBUTION TO DEFINING INTEGRITY TESTING IN POLICE – NORMATIVE ASPECTS Abstract: Integrity of an individual means their preparedness and capability to resist challenges which bring to the fore personal above general interests. From the aspect of work of civil servants who perform public authority, the integrity is in special relationship with corruption – the more integrity means less corruption and vice versa. As an investigative method, in the majority of cases integrity testing refers to police officers and it makes an integral part of a (new) methodology of suppressing corruption within their own ranks. In addition to revealing corruptive activities and testing legality of police officers’ conduct, integrity testing can be used to assess the quality of use of police powers.Although integrity testing has been in use in comparative law for several decades, it was introduced into Serbian legislation in 2016, by adopting the Law on Police. Initially impotent legal regulations required fast amendment, which suggested that integrity testing concept had not been understood well in our country. The paper defines the purpose and essence of integrity testing as an investigative method, it determines various modalities of its application, it presents comparative regulations and analyses normative solutions in our country. Special attention is directed at internal and external aspects of application of integrity testing results, particularly their significance in criminal procedure.
Keywords: Key words: integrity testing, police, corruption, simulated deals, Law on Police of the Republic of Serbia